PELAKSANAAN REMIDIAL TEACHING UNTUK MENINGKATKAN HASIL DAN PEMBELAJARAN MAHASISWA - Murwatiningsih, -; Sukirman, - (Dinamika Pendidikan, 2007)
the objective of this study is to improve the studentsÃ¢â¬â¢ learning activities by remedial teaching that used skill for asking question and giving reinforcement. This is a class action research with 55 students of Economics Education year 2006/2007, Semarang State University as the subject of research. The result of observation cycle I showed that there were several points that blocked learning design. Those are in ineffectual time allotment, crowded class situation and completing assignment dominated by only certain students. Learning activities have improved well and the number of active students who were brave to give opinion has also increased. At the end of cycle I showed that the number ofÃÂ  active students who could give opinion were 12 students (21.82%), students who submitted the assignment on time were 25 students (45.45%), the average of study result was 65.51 and the number of students who got score 71- 80 above were 30 students (54.54%). After remedial teaching, at the end of cycle II, the numbers of active students who asked and answered question and also gave opinion were 35 students (63.64%), students who submitted the assignment on time were 43 students (78.18%), the average score was 77.31 and the number of students who got score 71-80 above were 45 students (81.83%). Based on the result above, it can be concluded that the criteria of action success were (1) at least 60 % students were active to ask and answer questions or give opinions and (2) at least 70% students were on time to submit the assignment and (3) more than 60% students who gotÃÂ  score 71-80 above was reached. Keywords : Remidial Teaching, learning result